Gray's anatomy - Martinez, Cliff 1954- (<<The>> Criterion Collection, 2012)
One of the great raconteurs of stage and screen comes together with one of cinema's boldest image makers, Oscar winning director Steven Soderbergh for Gray's Anatomy, a spellbinding adaptation of Gray's 1993 monologue of the same name in which he chronicles his journey from diagnosis to treatment of a rare ocular condition
Original: USA, Großbritannien 1997
Special features include: Disc 1: new interviews with Soderbergh and monologue cowriter Renée Shafransky ; Swimming to the Macula : sixteen minutes of footage from Spalding Gray's actual eye surgery ; trailer. Disc 2. A personal history of the American Theater : a ninety-five-minute monologue by Gray, originally produced by the Wooster Group in 1980 and videotaped in 1982. - Accompanying booklet features essay by film critic Amy Toubin
Bildformat 1.85:1
Keywords: Gray, Spalding / 1941-2004; Gray, Spalding / 1941-2004 / Film adaptations; Gray, Spalding -- 1941-2004; Actors / United States; Eye / Diseases / Alternative treatment; Mortality; Augenkrankheit; Verfilmung; Schauspieler; Sterblichkeit; USA; Film; DVD-Video